The COBATEST network: monitoring and evaluation of HIV community‐based practices in Europe, 2014–2016. (28th February 2018) - Fernàndez‐López, L; Reyes‐Urueña, J; Agustí, C; Kustec, T; Serdt, M; Klavs, I; Casabona, J
Abstract : Objective: The objective of this paper is to describe the data collected by the CBVCT services from the Community‐based testing (COBATEST) network, from 2014 to 2016, in order to provide an insight into community‐based voluntary counselling and testing (CBVCT) services' testing activity in Europe. Methods: A descriptive analysis of HIV testing activity in CBVCT services that are using the COBATEST tools was performed for the period 2014–2016. Results: During the study period, a total of 30 329 HIV tests were performed on 27 934 individuals, of which 1.8% were reactive. Of these reactive tests, 75.8% had a confirmatory test, 92.2% of those were confirmed as positive, and 90.38% of the confirmed positives were linked to care. The total number of tests performed over the study period increased 19.31%. The proportion of confirmatory tests increased from 63.0% to 90.0% and proportion linked to care increased from 84.1% to 93.8%. Most of the tested individuals were men (70.6%), aged between 21 and 35 years (58.5%) and non‐foreign born (68.1%). A high proportion of individuals tested were men who have sex with men (MSM; 42.2%). The percentage of reactive screening tests was particularly high among transgender people (8.37%) and among male sex workers (6.38%). Repeat testers had a higher percentage of reactive tests (2.02%) than those tested for first time (1.1%). Conclusions: These results prove the feasibility of collecting standardized data from CBVCT services in different countries across Europe and demonstrate the usefulness of such data.